An unusual case of perisplenic small bowel volvulus after laparoscopic Roux En Y gastric bypass. Issue 2 (19th February 2019) - Sharma, Nitin; Chau, Wai Yip; Dobruskin, Lisa
Abstract: Internal hernias (IH) are one of the dreadful complications of laparoscopic Roux En Y gastric bypass (LGBP). Commonly reported internal hernias (IH) following Roux En Y gastric bypass (LGBP) in the literature are meso-colic, meso jejunal and Peterson's space hernias. These patients may not have any definitive symptoms. Findings are often missed on radiological studies and a high index of clinical suspicion is often necessary. If in doubt, a timely diagnostic laparoscopy is critical to decrease morbidity and mortality in these patients. We present a very unusual case of peri-splenic small bowel herniation with volvulus following LGBP with indeterminate radiological findings. Our case emphasizes that early laparoscopy is both diagnostic and therapeutic for desirable clinical outcomes.